Correção do solo e sistemas de rotação de culturas sobre a absorção de nutrientes e produção de soja - CAETANO, Jeander Oliveira (2011)
Crop rotation and the increase in straw on the soil are among the main requirements for the implementation and maintenance of no-tillage in the Cerrado. The use of integrated crop and livestock production, coupled with the introduction of Brachiaria in agricultural areas has helped to maintain this coverage and increased amounts of plant species as alternatives to rotation. Thus, there is a need to evaluate these cover crops and forms of fertility management which are widely used by farmers in Brazil. The aim was to evaluate the effect of two forms of soil correction, four types of soil cover and four levels of KCl on production and nutrient content of aerial part dry biomass of soil cover types, the yield and content soybean leaf nutrient and chemical attributes of an Oxisol. The experimental was arranged in a randomized block design, with four replications, the field was laid out in 2x4x4 and arranged in strip-split plot design. Was evaluated the forms of soil correction initial total and annual installment (main plot), the types of soil cover Brachiaria brizantha, B. ruziziensis, sorghum crop residues and spontaneous vegetation (subplots) and the levels of KCl correspondents to 0 kg ha-1, 20 kg ha-1, 40 kg ha-1 e 60 kg ha-1 of K2O (subsubplots). On the soil, for the depths 0-20 cm and 20-40 cm analyzed the pH CaCl2, organic matter, exchangeable Ca, Mg, K and Al, H+Al and the contents of available P, Fe, Mn, Cu and Zn. In the leaves were determined N, P, K, Ca, Mg, Fe, Mn, Cu and Zn. Was collected dry biomass of soil cover and estimated soybean yield. The forms of soil correction initial total and annual installment not influence soybean yield. B. brizantha produces highest biomass, which occurs in the highest soybean yield. Potassium is the nutrient of greatest accumulation in leaf of B. brizantha and B. ruziziensis. The increasing levels of KCl do not affect the soybean yield. The soybean yield is more affected by the kind of cover crops than by the form of correction and levels of potassium.